Cordel literature and environmental narratives (Revista Internacional de Folkcomunicação, 2019)
In this article, we try to reflect on the cordel literature, visualized as a channel of folkcommunication for the construction of narratives that address the environmental issues. Accessible to the popular classes and with simple language, the cordel is able to approach several themes with humor and creativity, important elements for the construction of narratives that, more than simply informational, may have repercussions and be more perennial and transformative. Our method consisted essentially in exploring the narrative level of the selected cordels. Cordel literature; Folkcommunication; Environmental education; Environmental narratives.